A method for preparing TPU gloves

By adding zinc oxide aerogel particles to the TPU gloves and molding them by impregnation method, the problem of poor breathability of TPU gloves is solved, and higher breathability and antibacterial performance is achieved, which improves the wearer's comfort and the functionality of the gloves.

CN119432046BActive Publication Date: 2025-03-28SHANDONG INTE MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510040592.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing TPU gloves have poor breathability, causing the wearer to feel stuffy and uncomfortable during prolonged use, which may cause skin problems and medical risks.

Method used

By adding zinc oxide aerogel particles to the preparation process of TPU gloves and molding by impregnation method, a microporous structure is formed to improve breathability, and at the same time, the antibacterial properties of zinc oxide are used to enhance protective performance.

Benefits of technology

It significantly improves the breathability and antibacterial properties of TPU gloves, improves the wearer's comfort and the functionality of the gloves, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of medical devices, and specifically proposes a method for preparing TPU gloves, wherein the TPU uses zinc oxide aerogel particles as a modified filler, which is added to a TPU impregnated material. After zinc oxide aerogel particles with an average particle size of 50-500nm are used as fillers, the air permeability and antibacterial properties of the TPU gloves are greatly improved. The technology not only improves the comfort and functionality of the gloves, but is also suitable for large-scale production, and has significant economic value and market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical devices, and in particular to a method for preparing TPU gloves. Background Art

[0002] With the increasing demand for gloves in the medical, nursing, food processing and industrial fields, gloves play a vital role as personal protective equipment in daily work and life. In these applications, medical gloves are particularly important. They need to provide protection against the invasion of bacteria, viruses and chemicals, and also need to ensure comfort, breathability and mechanical properties. However, existing medical gloves, especially polyurethane-based gloves, have the advantages of wear resistance, biocompatibility, and no allergic reactions, and have been widely used in the medical field, but they generally face the following problems.

[0003] Since TPU is a polymer formed by the reaction of isocyanate and polyol, it has a relatively tight molecular structure and the interaction between its molecular chains is strong, resulting in a low degree of freedom of the molecular chains and difficulty in forming a sufficient pore structure. Therefore, the air permeability of ordinary TPU gloves is poor, and the wearer is prone to feel stuffy and airtight during long-term use, which causes discomfort. Poor air permeability of gloves often leads to sweat accumulation, affecting skin comfort, and may cause eczema and other skin problems. It is also easy to bring other potential medical risks.

[0004] How to improve the air permeability of TPU gloves has become one of the technical problems that need to be solved urgently. Summary of the invention

[0005] In view of this, the present invention proposes a method for preparing TPU gloves, aiming to improve the air permeability of TPU gloves and enhance the comfort of users by optimizing the preparation process of TPU gloves.

[0006] The technical solution of the present invention is achieved as follows: The present invention provides a method for preparing TPU gloves, comprising the following steps:

[0007] Step 1: Heat the TPU particles to a molten state, slowly add the zinc oxide aerogel particles while stirring, stir evenly, and obtain an impregnation material, wherein the mass ratio of the zinc oxide aerogel particles to the TPU particles is 1-30%;

[0008] Step 2: Using the dipping method, immerse the heated hand mold into the dipping material at 160-180°C for 10-30s, lift the mold and cool it to 20-30°C, and demould to obtain the TPU gloves;

[0009] The average particle size of the zinc oxide aerogel particles is 50-500 nm.

[0010] Zinc oxide aerogel particles are used as functional filler components. Zinc oxide aerogel particles have a high specific surface area and low density, which enables them to form a microporous structure in the TPU matrix, thereby improving the air permeability of TPU gloves. In addition, zinc oxide itself has good antibacterial properties, which can effectively inhibit the growth of bacteria and viruses and increase the protective performance of gloves.

[0011] In some embodiments, the method for preparing zinc oxide aerogel particles comprises:

[0012] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+ : The molar ratio of sodium citrate is 1:2, and stirring is uniform to form a precursor solution;

[0013] Slowly add ammonia water to the precursor solution under stirring to adjust the pH value to 6-7, and then let it stand for 12-18 hours to form a wet gel;

[0014] The wet gel was aged at 50-60°C for 20-30h, and then washed with deionized water 1-3 times;

[0015] Soak the washed wet gel in ethanol or isopropanol for solvent exchange 3-5 times, each time for 6 hours;

[0016] The wet gel after solvent exchange treatment is subjected to supercritical CO2 drying at a supercritical drying temperature of 40-50°C, a pressure of 10-15MPa, and a time of 6-8h;

[0017] The dried aerogel is placed in a muffle furnace and calcined for 2-3 hours at a calcination temperature of 350-400° C. After calcination, the aerogel is ground to obtain zinc oxide aerogel particles.

[0018] The zinc oxide aerogel particles prepared by the above method have a pore size range of 2-10nm, which can only allow gas and water molecules to pass through, effectively blocking bacteria and viruses. The nanopore structure is combined with the antibacterial properties of zinc oxide to provide excellent protective performance and air permeability. Moreover, the aerogel particles have a stable structure and can effectively maintain stability under different temperature and humidity conditions.

[0019] In some embodiments, the aerogel particles are surface modified, and the modification method includes adding the dried zinc oxide aerogel particles to an ethanol solution of a silane coupling agent with a mass concentration of 1-3% at a solid-liquid ratio of 1:10, reflux treatment at 50-70° C. for 4-6 hours, filtering and drying to obtain modified zinc oxide aerogel particles.

[0020] In some embodiments, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.

[0021] In order to further improve the composite effect, the surface modification treatment uses silane coupling agent for modification, which can enhance the interfacial bonding force between zinc oxide aerogel particles and TPU matrix, thereby improving the dispersion and composite effect of particles. The introduction of silane coupling agent can form functional groups with strong affinity on the surface of particles, improve the compatibility of particles and TPU, avoid interface shedding or particle damage, and ensure the stability and antibacterial properties of gloves during use.

[0022] In some embodiments, in step one, before being added to the molten TPU, the zinc oxide aerogel particles are subjected to a composite treatment, and the composite treatment method comprises: placing the zinc oxide aerogel particles and a thermoplastic polyester elastomer into a twin-screw extruder, blending and extruding to obtain composite particles, and freeze-grinding the composite particles to form composite material particles with an average particle size of 1-5 μm.

[0023] Since zinc oxide aerogel particles have poor dispersibility in the TPU matrix, they are prone to agglomeration, which limits the mechanical properties and air permeability of the material. Therefore, in the present invention, a treatment method of compounding zinc oxide aerogel particles with thermoplastic polyester elastomer (TPE-E) is adopted. Through co-extrusion, the compatibility of zinc oxide aerogel particles with the TPU matrix can be effectively improved, particle agglomeration can be avoided, and the dispersion effect can be improved. The composite particles can also avoid stress concentration of zinc oxide aerogel in TPU gloves, thereby improving the mechanical properties of the gloves.

[0024] In some embodiments, the mass ratio of zinc oxide aerogel particles to thermoplastic polyester elastomer is 10-30%.

[0025] In some embodiments, the melt blending temperature is 190-220° C., the mixing time is 3-10 min, and the rotation speed is 100-300 rpm.

[0026] In some embodiments, the cryo-grinding temperature is between -70°C and -120°C.

[0027] In some embodiments, in step 2, the hand mold is heated to a temperature of 60-80°C.

[0028] The present invention also provides a TPU glove prepared by the preparation method.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention successfully improves the air permeability and antibacterial properties of TPU gloves by compounding zinc oxide aerogel particles with TPU materials and adopting a preparation method of dipping molding. This technology not only improves the comfort and functionality of the gloves, but is also suitable for large-scale production and has significant economic value and market prospects. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0033] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0034] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0035] The technical solution of the present application is further described below through specific embodiments.

[0036] Example 1

[0037] This embodiment uses commercially available 30D TPU particles and commercially available zinc oxide aerogel particles with an average particle size of 200 nm as raw materials.

[0038] Heat the TPU particles to 170°C and stir until they are molten. Slowly add the commercially available zinc oxide aerogel particles under stirring and stir evenly to obtain the impregnation material. The mass ratio of zinc oxide aerogel to TPU is 5%. Dip the hand mold heated to 70°C into the 170°C impregnation material, let it stand for 20 seconds, lift the hand mold and slowly rotate it to make the glue evenly impregnate the surface of the hand mold, and cool it to 25°C at the same time. Demold to obtain the TPU gloves.

[0039] Example 2

[0040] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials.

[0041] Preparation of zinc oxide aerogel particles:

[0042] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+ The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0043] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared zinc oxide aerogel particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and then cooled to 25°C and demolded to obtain the TPU gloves.

[0044] Example 3

[0045] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0046] Preparation of zinc oxide aerogel particles:

[0047] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0048] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0049] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0050] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0051] Example 4

[0052] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0053] Preparation of zinc oxide aerogel particles:

[0054] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0055] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0056] The zinc oxide aerogel particles were heated to 100°C for drying to constant weight, then cooled to room temperature, added to an anhydrous ethanol solution of γ-aminopropyltriethoxysilane with a mass concentration of 2% at a solid-liquid ratio of 1:10, heated to 60°C for reflux treatment for 5 hours, filtered and dried to obtain modified zinc oxide aerogel particles, and the modified zinc oxide aerogel particles and thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, the temperature was set to 210°C, the speed was 250rpm, the mixing time was 5min, and the composite particles were obtained by blending and extrusion. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3μm.

[0057] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0058] Example 5

[0059] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0060] Preparation of zinc oxide aerogel particles:

[0061] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0062] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0063] The zinc oxide aerogel particles were heated to 100°C for drying to constant weight, then cooled to room temperature, added to an anhydrous ethanol solution containing 2wt% 3-aminopropyltrimethoxysilane at a solid-liquid ratio of 1:10, heated to 60°C for reflux treatment for 5h, filtered and dried to obtain modified zinc oxide aerogel particles, and the modified zinc oxide aerogel particles and thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, the temperature was set to 210°C, the speed was 250rpm, the mixing time was 5min, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3μm.

[0064] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0065] Example 6

[0066] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0067] Preparation of zinc oxide aerogel particles:

[0068] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0069] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0070] The zinc oxide aerogel particles were heated to 100°C for drying to constant weight, then cooled to room temperature, added to an anhydrous ethanol solution containing 1wt% of γ-aminopropyltriethoxysilane and 1wt% of 3-aminopropyltrimethoxysilane at a solid-liquid ratio of 1:10, heated to 60°C for reflux treatment for 5h, filtered and dried to obtain modified zinc oxide aerogel particles, and the modified zinc oxide aerogel particles and thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, the temperature was set to 210°C, the speed was 250rpm, the mixing time was 5min, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3μm.

[0071] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0072] Example 7

[0073] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0074] Preparation of zinc oxide aerogel particles:

[0075] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to water is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5, and then the solution is allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours, and then washed with deionized water for 3 times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated 3 times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 50nm.

[0076] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0077] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0078] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0079] Example 8

[0080] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0081] Preparation of zinc oxide aerogel particles:

[0082] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 500nm.

[0083] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0084] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0085] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0086] Example 9

[0087] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0088] Preparation of zinc oxide aerogel particles:

[0089] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0090] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0091] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 1 μm.

[0092] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0093] Example 10

[0094] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0095] Preparation of zinc oxide aerogel particles:

[0096] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0097] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0098] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 5 μm.

[0099] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0100] Embodiment 11

[0101] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0102] Preparation of zinc oxide aerogel particles:

[0103] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 6.0, and then the solution is allowed to stand for 12 hours to form a wet gel. The wet gel is aged at 50°C for 30 hours, and then washed once with deionized water. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is performed 5 times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40°C and a drying pressure of 10 MPa for 8 hours. The aerogel obtained after drying is heated to 350°C in a muffle furnace and calcined for 3 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200 nm.

[0104] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0105] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 10%, and the temperature was set at 190°C, the speed was 100 rpm, and the mixing time was 10 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -70°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0106] The TPU particles were heated to 160°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 1%. The hand mold heated to 60°C was immersed in the 160°C impregnation material, and the impregnation was allowed to stand for 30 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 20°C at the same time, and demolded to obtain the TPU gloves.

[0107] Example 12

[0108] This embodiment uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer.

[0109] Preparation of zinc oxide aerogel particles:

[0110] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to sodium citrate is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 7, and then the solution is allowed to stand for 18 hours to form a wet gel. The wet gel is aged at 60°C for 20 hours, and then washed with deionized water for 3 times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is performed 3 times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 50°C and a drying pressure of 13 MPa for 6 hours. The aerogel obtained after drying is heated to 380°C in a muffle furnace and calcined for 2 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200 nm.

[0111] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0112] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 30%, and the temperature was set at 220°C, the speed was 300 rpm, and the mixing time was 3 minutes for co-extrusion to obtain composite particles. The obtained composite particles were frozen to -120°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0113] The TPU particles were heated to 180°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, wherein the mass ratio of zinc oxide aerogel to TPU was 30%. The hand mold heated to 80°C was immersed in the 180°C impregnation material, and the impregnation was allowed to stand for 10 seconds. The hand mold was lifted and then slowly rotated to allow the glue to be evenly impregnated on the surface of the hand mold, and then cooled to 30°C and demolded to obtain the TPU gloves.

[0114] Comparative Example 1

[0115] This comparative example uses commercially available 30D TPU particles as raw materials.

[0116] Heat the TPU particles to 170°C, stir until they are molten, and stir evenly to obtain the impregnation material. Dip the hand mold heated to 70°C into the impregnation material at 170°C, let it stand for 20 seconds, lift the hand mold and slowly rotate it to make the glue evenly impregnate the surface of the hand mold, and cool it to 25°C at the same time, demould it to obtain the TPU gloves.

[0117] Comparative Example 2

[0118] This comparative example uses commercially available 30D TPU particles and commercially available silica aerogel particles with an average particle size of 200 nm as raw materials.

[0119] Heat the TPU particles to 170°C and stir until they are molten. Slowly add the commercially available silica aerogel particles under stirring and stir evenly to obtain the impregnation material. The mass ratio of silica aerogel to TPU is 5%. Dip the hand mold heated to 70°C into the 170°C impregnation material, let it stand for 20 seconds, lift the hand mold and slowly rotate it to make the glue evenly impregnate the surface of the hand mold, and cool it to 25°C at the same time. De-mold to obtain the TPU gloves.

[0120] Comparative Example 3

[0121] This embodiment uses commercially available 30D TPU particles, homemade zinc oxide aerogel particles and thermoplastic polyester elastomer as raw materials, and the zinc oxide aerogel particles are not compounded with the thermoplastic polyester elastomer.

[0122] Preparation of zinc oxide aerogel particles:

[0123] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+ The molar ratio of sodium citrate to sodium citrate is 1:2. After stirring evenly, a precursor solution is obtained. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5. The solution is then allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours. The wet gel is then washed with deionized water for three times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated three times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours. The aerogel is then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 200nm.

[0124] Preparation of thermoplastic polyester elastomer granules:

[0125] The thermoplastic polyester elastomer was added to a twin-screw extruder, and the temperature was set to 210°C, the rotation speed was 250 rpm, and the mixing time was 5 minutes, and a blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain thermoplastic polyester elastomer particles with an average particle size of 3 μm.

[0126] Heat the TPU particles to 170°C and stir until they are molten. Slowly add the prepared composite material particles under stirring and stir evenly to obtain the impregnation material, (zinc oxide aerogel + thermoplastic polyester elastomer particles): TPU mass ratio is 5%, wherein the mass ratio of zinc oxide aerogel: thermoplastic polyester elastomer particles is 15%. Immerse the hand mold heated to 70°C into the impregnation material at 170°C, let it stand for 20 seconds, lift the hand mold and slowly rotate it to make the glue solution evenly impregnate the surface of the hand mold, and cool it to 25°C at the same time, demould to obtain the TPU gloves.

[0127] Comparative Example 4

[0128] This comparative example uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer, and the homemade zinc oxide aerogel particles have a smaller average particle size (40 nm).

[0129] Preparation of zinc oxide aerogel particles:

[0130] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+ The molar ratio of sodium citrate to water is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5, and then the solution is allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours, and then washed with deionized water for 3 times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated 3 times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 40nm.

[0131] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0132] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0133] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0134] Comparative Example 5

[0135] This comparative example uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are compounded with a thermoplastic polyester elastomer, and the homemade zinc oxide aerogel particles have a larger average particle size (600 nm).

[0136] Preparation of zinc oxide aerogel particles:

[0137] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+ The molar ratio of sodium citrate to sodium citrate is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5, and then the solution is allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours, and then washed with deionized water for 3 times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is performed 3 times. The wet gel after the exchange treatment is subjected to supercritical CO2 drying at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 600nm.

[0138] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0139] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 3 μm.

[0140] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0141] Comparative Example 6

[0142] This comparative example uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are composited with a thermoplastic polyester elastomer, and the composite particles have a smaller average particle size (500 nm).

[0143] Preparation of zinc oxide aerogel particles:

[0144] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to water is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5, and then the solution is allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours, and then washed with deionized water for 3 times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated 3 times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 40nm.

[0145] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0146] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 500 nm.

[0147] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0148] Comparative Example 7

[0149] This comparative example uses commercially available 30D TPU particles and homemade zinc oxide aerogel particles as raw materials, wherein the homemade zinc oxide aerogel particles are composited with a thermoplastic polyester elastomer, and the composite particles have a larger average particle size (10 μm).

[0150] Preparation of zinc oxide aerogel particles:

[0151] Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+The molar ratio of sodium citrate to water is 1:2, and a precursor solution is obtained after stirring evenly. Ammonia water is added dropwise while stirring to adjust the pH value to 6.5, and then the solution is allowed to stand for 16 hours to form a wet gel. The wet gel is aged at 55°C for 25 hours, and then washed with deionized water for 3 times. The washed wet gel is immersed in ethanol for solvent exchange treatment, each time for 6 hours, and the exchange treatment is repeated 3 times. The wet gel after the exchange treatment is dried by supercritical CO2 at a drying temperature of 40-50°C and a drying pressure of 15MPa for 7 hours. The aerogel obtained after drying is heated to 370°C in a muffle furnace and calcined for 2.5 hours, and then ground and sieved to obtain zinc oxide aerogel particles with an average particle size of 40nm.

[0152] Preparation of zinc oxide aerogel-thermoplastic polyester elastomer composite particles:

[0153] The zinc oxide aerogel particles and the thermoplastic polyester elastomer were added to a twin-screw extruder at a mass ratio of 15%, and the temperature was set to 210°C, the speed was 250 rpm, and the mixing time was 5 minutes, and the blending extrusion process was performed to obtain composite particles. The obtained composite particles were frozen to -80°C and then ground and sieved to obtain composite material particles with an average particle size of 10 μm.

[0154] The TPU particles were heated to 170°C and stirred until they were molten. Under stirring conditions, the prepared composite material particles were slowly added and stirred evenly to obtain an impregnation material, with a mass ratio of zinc oxide aerogel to TPU of 5%. The hand mold heated to 70°C was immersed in the 170°C impregnation material, and the impregnation was allowed to stand for 20 seconds. The hand mold was lifted and then slowly rotated to evenly impregnate the glue on the surface of the hand mold, and cooled to 25°C at the same time, and demolded to obtain the TPU gloves.

[0155] The TPU gloves prepared based on the above examples and comparative examples were tested for tensile strength, air permeability, antibacterial properties, comfort and dimensional stability. The test results are shown in the following table:

[0156]

[0157] By comparing the data of Example 1 with that of Comparative Example 1, it can be seen that after the TPU gloves are modified by using zinc oxide aerogel particles as fillers, the air permeability of the gloves can be greatly improved, but the tensile strength and dimensional stability are reduced to a certain extent.

[0158] In Example 2, zinc oxide aerogel prepared by an optimized process is used as a filler to replace conventional commercially available aerogel. Compared with Example 1, the tensile strength, air permeability and dimensional stability are slightly improved, and compared with a single TPU glove, the dimensional stability is closer.

[0159] In Example 3, zinc oxide aerogel particles and thermoplastic polyester elastomer are pre-compounded to prepare a composite particle structure, which is directly used for filling and modification of TPU instead of zinc oxide aerogel. Compared with Example 2, it can be seen that the performance in various aspects is significantly improved, especially the air permeability, comfort and dimensional stability.

[0160] Before the composite treatment, the zinc oxide aerogels in Examples 4, 5 and 6 were subjected to surface modification. It can be seen that after the surface modification treatment, the air permeability and comfort of Examples 4 and 5 decreased to a certain extent compared with Example 3. It is considered that the introduction of the composite structure leads to a decrease in the effective channels in the zinc oxide aerogels, and the composite particles are larger in size and have poor dispersibility in the TPU matrix. However, Example 6 improves the air permeability and comfort, and other properties are better than those in Example 3. It is considered that the specific combination of silane coupling agents is modified to optimize the dispersibility of the zinc oxide aerogel in the composite particles, which not only ensures the air permeability channels, but also improves the mechanical properties and comfort after better dispersibility.

[0161] Examples 7-12 respectively demonstrate the performance of TPU gloves at different aerogel particle sizes and composite particle sizes. Compared with Comparative Example 1, they all show good use effects, especially air permeability.

[0162] It can be seen from Example 3 and Comparative Example 3 that even under the same raw material conditions, the performance of Example 3 is far superior to that of Comparative Example 3, indicating that in the preparation method of the present application, the method of compounding zinc oxide aerogel particles with thermoplastic polyester elastomer has outstanding technical effects.

[0163] Compared with Comparative Example 2, it can be seen that the zinc oxide aerogel particles used for filling cannot be replaced by conventional aerogel particles.

[0164] Comparative Examples 4-7 respectively used zinc oxide aerogel particles and composite particles of different sizes, and the effects were far inferior to those of Examples 3 and Examples 7-10, indicating that the specific particle size of zinc oxide aerogel particles and composite particles is a prerequisite for ensuring the excellent technical effect of TPU.

[0165] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing TPU gloves, characterized in that: The steps include: Step 1: Heat the TPU particles to a molten state, slowly add the zinc oxide aerogel particles while stirring, stir evenly, and obtain an impregnation material, wherein the mass ratio of the zinc oxide aerogel particles to the TPU particles is 1-30%; Step 2: Using the dipping method, immerse the heated hand mold into the dipping material at 160-180°C for 10-30s, lift the mold and cool it to 20-30°C, and demould to obtain the TPU gloves; The average particle size of the zinc oxide aerogel particles is 50-500 nm.

2. The method for preparing TPU gloves according to claim 1, characterized in that: The preparation method of the zinc oxide aerogel particles comprises: Add sodium citrate to 0.1 mol / L zinc nitrate solution. 2+ : The molar ratio of sodium citrate is 1:2, and stirring is uniform to form a precursor solution; Slowly add ammonia water to the precursor solution under stirring to adjust the pH value to 6-7, and then let it stand for 12-18 hours to form a wet gel; The wet gel was aged at 50-60°C for 20-30h, and then washed with deionized water 1-3 times; Soak the washed wet gel in ethanol or isopropanol for solvent exchange 3-5 times, each time for 6 hours; The wet gel after solvent exchange treatment is subjected to supercritical CO2 drying at a supercritical drying temperature of 40-50°C, a pressure of 10-15MPa, and a time of 6-8h; The dried aerogel is placed in a muffle furnace and calcined for 2-3 hours at a calcination temperature of 350-400° C. After calcination, the aerogel is ground to obtain zinc oxide aerogel particles.

3. The method for preparing TPU gloves according to claim 1, characterized in that: The aerogel particles are subjected to surface modification treatment, and the modification treatment method includes adding the dried zinc oxide aerogel particles to an ethanol solution of a silane coupling agent with a mass concentration of 1-3% at a solid-liquid ratio of 1:10, reflux treatment at 50-70°C for 4-6h, filtering and drying to obtain modified zinc oxide aerogel particles.

4. The method for preparing TPU gloves according to claim 3, characterized in that: The silane coupling agent is at least one of γ-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.

5. The method for preparing TPU gloves according to claim 1, characterized in that: In step one, before being added to the molten TPU, the zinc oxide aerogel particles are subjected to a composite treatment, and the composite treatment method comprises: placing the zinc oxide aerogel particles and a thermoplastic polyester elastomer into a twin-screw extruder, blending and extruding to obtain composite particles, and freeze-grinding the composite particles to form composite material particles with an average particle size of 1-5 μm.

6. The method for preparing TPU gloves according to claim 5, characterized in that: The mass ratio of zinc oxide aerogel particles to thermoplastic polyester elastomer is 10-30%.

7. The method for preparing TPU gloves according to claim 5, characterized in that: The temperature of melt blending is 190-220°C, the mixing time is 3-10min, and the rotation speed is 100-300rpm.

8. The method for preparing TPU gloves according to claim 5, characterized in that: The freezing grinding temperature is -70℃~-120℃.

9. The method for preparing TPU gloves according to claim 1, characterized in that: In step 2, the hand mold is heated to a temperature of 60-80°C.

10. A TPU glove, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Zinc oxide / reduced graphene oxide aerogel and preparation method of zinc oxide / reduced graphene oxide aerogel

    CN105749896A

  • Preparation method of self-cleaning finishing agent for polyester-cotton fabrics

    CN109267329A